Gods, games, and the socioecological landscape - Benjamin Grant Purzycki; Theiss Bendixen; Aaron D. Lightner; Richard Sosis (Current Research in Ecological and Social Psychology, 2022)
The social sciences have long recognized a relationship between religion and social ecology. Upon closer inspection, religious systems not only correspond to important features of a society’s social ecology, but also appear to directly address these features. In this article, we examine the prospect that these salient features may be framed as game theoretical dilemmas and argue that contemporary approaches that emphasize cognition and/or social learning at the expense of social ecology are inadequate in accounting for cross-cultural variation in religious expression. Using ethnographic examples, we show that religions alleviate the costs of such dilemmas in a variety of ways by: 1) fostering beliefs that motivate and sustain beneficial practices; 2) incentivizing cooperative ventures; 3) encouraging ritual performances that minimize costly conflicts and bolster territorial conventions; 4) providing institutional forums to coordinate resource distributions; and 5) maintaining important resource and species diversity.